2016
DOI: 10.1097/md.0000000000004841
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of sudden sensorineural hearing loss in stroke patients

Abstract: Poststroke sudden sensorineural hearing loss (SSNHL) can hinder communication between patients and healthcare professionals, thereby restricting participation in rehabilitation programs and limiting improvements in physical performance. However, the relationship between stroke and SSNHL remains unclear. This study employed a nationwide population-based dataset to investigate the relationship between stroke and SSNHL.The Taiwan Longitudinal Health Insurance Database was used to compile data from 11,115 stroke p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 28 publications
(43 reference statements)
3
18
1
Order By: Relevance
“…This finding suggests that SSNHL may be an early indicator of stroke . Furthermore, another nationwide cohort study found that patients with stroke had a higher risk of subsequent SSNHL . It is clear from these studies that there is a link between SSNHL and cerebrovascular disease; however, the relationship between SSNHL and cardiocerebrovascular disease (CCVD) still has yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that SSNHL may be an early indicator of stroke . Furthermore, another nationwide cohort study found that patients with stroke had a higher risk of subsequent SSNHL . It is clear from these studies that there is a link between SSNHL and cerebrovascular disease; however, the relationship between SSNHL and cardiocerebrovascular disease (CCVD) still has yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…mumps virus), intralabyrinthine hemorrhage and rupture of the labyrinthine window have been reported as causes of SSNHL 7 , 18 20 . Previous studies have suggested that risk factors for cerebrovascular and cardiovascular disease can also be considered risk factors for idiopathic SSNHL 21 , 22 . Although previous studies have provided evidence for the hypothesis that idiopathic SSNHL is caused by a circulatory disturbance 2 4 , like cochlear infarction, no definitive conclusions have been reached.…”
Section: Discussionmentioning
confidence: 99%
“…Some experts favor viral infection as the main cause of SHL on the basis of viral polymerase chain reaction 23 and pathological findings. 24 However, other lines of evidence suggest a vascular etiology, including mechanisms (increase of prothrombin factors in patients with SHL 25 ) and an epidemiological association with stroke (history of stroke as a risk factor for SHL 26 and increased risk of stroke during 5-year follow-up [HR = 1.64] 11 ). Case reports and case series data suggest SHL can be a prodromal warning sign for a large-vessel disease (AICA infarction, 27 basilar artery occlusion, 28 or, rarely, even posterior inferior cerebellar artery [PICA] infarction 29 ).…”
Section: Discussionmentioning
confidence: 99%